Calculation of Air Gap Magnetic Field and Torque of Dual-modulation Axial Magnet Gear Motors - Ge Yanjun; Ma Xueqi; Li Haitao; Long Wei; Yu Han (Jixie chuandong)
A dual-modulation axial magnet gear motor （DAMGM） was proposed to address the shortcomings of the axial magnet gear motor （AMGM）, which has a large overall size and low torque density（≤70 kN·m/m3）. Two magnetizing rings on the high-speed and low-speed sides were used to modulate the low-speed rotor in the DAMGM, and the non-magnetic parts in both magnetic magnetizing rings were permanent magnets, effectively improving the output torque of the low-speed rotor. In addition, compared to the existing AMGM, the drive motor was placed inside the high-speed permanent magnet rotor of the DAMGM, reducing the overall axial size and significantly improving the torque density of the low-speed rotor（150 kN·m/m3）. Aiming at the problems of long calculation time and serious waste of computer resources in the existing 3D finite element method, a 3D analysis method of DAMGM based on the cylindrical coordinate system was presented. According to three boundary conditions of the magnetizing ring, the mathematical and physical models of the modulated DAMGM air gap magnetic field and electromagnetic torque were established. The calculation results are not only accurate （compared with the 3D finite element method, the average calculation error is less than or equal to 5%）, but also the calculation time is short （only 1/10 of the 3D finite element method）, facilitating the analysis, comparison, and optimization of different parameter structures in the DAMGM.